American authors and the literary marketplace since 1900 - West, James L. W., III (Publication of the A.S.W. Rosenbach fellowship in bibliography., 1990)
This book examines literary authorship in the twentieth century and covers such topics as publishing, book distribution, the trade editor, the literary agent, the magazine market, subsidiary rights, and the blockbuster mentality.